Impact of frozen elephant trunk on the outcomes of thoracoabdominal aortic repair with normothermic iliac perfusion - Gao, Haoyu; Wang, Luchen; Liu, Yanxiang; Liang, Shenghua; Zhang, Bowen; Ren, Jie; Yu, Cuntao; Sun, Xiaogang (Frontiers in Surgery, 2023)
Background: Frozen elephant trunk technique (FET) has been proven to provide an excellent landing zone for second-stage thoracoabdominal (TA) aortic repair. The aim of this study was to evaluate the impact of FET in TA aortic repair with normothermic iliac perfusion. Methods: From January 2008 to December 2019, 144 patients undergoing TA repair with normothermic iliac perfusion were enrolled in this study. Early and mid-term outcomes of patients with previous FET implantation (group A, n = 62) were compared with patients without previous FET implantation (group B, n = 82). The logistic regression analysis was performed to investigate the risk factors for adverse events, which were deﬁned as early death, permanent stroke, permanent paraplegia, or permanent renal failure necessitating dialysis. Results: The proximal aortic clamp time and operating time was 14.26 ± 5.57 min and 357.40 ± 94.51 respectively in group A, which were both significantly shorter than that in group B (18.67 ± 5.24min and 18.67 ± 5.24 min). The incidence of adverse event was significantly lower in group A than that in group B (9.7% vs 25.6%, P = 0.027). There was no significant difference between two groups with regard to other complications or late outcomes. In addition, age >50 y, a Ccr < 90 ml/min/1.73 m2 and the operating time were identified as significant risk factors through logistic regression analysis for adverse events of TA repair. Conclusions: The FET technique simplifies the operative technique of proximal anastomosis, decreases the operating time and improves the early outcomes in TA repair, whereas does not provide a significant benefit with regard to late outcomes. Long-term follow-up and studies with larger sample sizes are necessary for further confirmation.